(untitled) (International Journal of Irrigation and Water Management, 2014)
A study was conducted during 2009 to 2010 and 2010 to 2011 to find out the effect of irrigation and fertigation scheduling on growth and yield of guava (Psidium guajava L.). The experiments were laid out in factorial randomized block design with sixteen treatment combinations which included four irrigation levels (basin, 50, 75 and 100% irrigation of irrigation water/cumulative pan evaporation) along with four fertigation levels, including, basal dose, 50, 75 and 100% water soluble fertilizers and replicated thrice. The nitrogen, phosphorus and potassium (NPK) fertilizers were applied through fertigation as well as soil application to test various attributes of 3-years-old guava cv. Shweta under meadow (ultra high density) orcharding. The investigation indicated that 100% irrigation of irrigation water/cumulative pan evaporation (I3) through drip resulted in maximum plant height (1.97 m), canopy volume (0.98 m3 ), girth of primary branches (2.41 cm), leaf area (62.94 cm2 ) and fruit weight (163.71 g). However, I2 (75% irrigation of irrigation water/cumulative pan evaporation) resulted in maximum plant spread east west north south (1.91 to 1.79 m), fruit yield/plant (5.87 kg) with benefit:cost ratio of 2.62. Use of 60, 30 and 30 g NPK/plant/year produced maximum leaf area (63.39 cm2 ), fruit weight (162.43 g) and fruit yield/plant (6.01 kg). Interaction effect of irrigation and fertigation levels showed that 100% irrigation of irrigation water/cumulative pan evaporation + 100% water soluble fertilizers gave maximum plant height (2.07 m), canopy volume (1.24 m3 ), girth of primary branches (2.48 cm), leaf area (66.08 cm2 ), fruit diameter 6.69 cm (polar) and 5.97 cm (equatorial), fruit weight (182.17 g), yield/plant (6.59 kg). However, maximum benefit:cost ratio of (2.91) was obtained as 75% irrigation of irrigation water/cumulative pan evaporation + 75% water soluble fertilizers.